Improving the new product/service introduction process by the application of system dynamics - Antonaras, A. (Cranfield University, 1999)
The development and marketing of new products and services are amongst the most powerful weapons that organisations can'use in order to survive and prosper under turbulent global market conditions. The successful introduction of a new product or service can assist an organisation to remain competitive by being able to sufficiently address the continuously changing market requirements. Therefore, the process of New Product / Service Introduction (NP/SI) constitutes a crucial activity for every organisation. In an environment of ever shortening product life cycles, increased customer expectation, technology advancements and increased market competition, the only factor that remains constant within a modem manufacturing operation is change. Such changes are ultimately reflected in the products and the manufacturing processes. One particular type of change apparent within a manufacturing or assembly environment is engineering change (EQ. The changes or modifications in forms, fits, materials, dimensions, functions, etc. of a product or component are usually referred to as ECs. The aims of this thesis were fulfilled by using the technique of System Dynamics (SD) in order to model and simulate the generic structure of the NP/Sl process and to identify ways to improve it. The results of the simulation were also used for developing an Engineering Change Management System which was then modelled by using the same technique of SD. In this attempt, two Greek organisations collaborated by providing data and information in order to investigate the existence of a cost-time-quality relationship throughout the NP/SI process.